ANXIETY OF BERNARD FINE IN DANIELLE STEEL'S FINE THINGS:A PSYCHOANALYTIC APPROACH - KUSUMAWATI, CATUR YANI MEI (2007)
The object of the research is the novel entitled Fine things by Danielle Steel. The study gives focus on anxiety of Bernard Fine in Danielle Steels Fine Things. The aim of the study are: 1) To analyze the novel based on the structural elements of the novel. 2) To analyze the anxiety of the major character based on the psychoanalytic perspective. The analysis uses descriptive qualitative by describing the structural elements and psychoanalytic analysis. The approach uses psychoanalytic theory. The primary source of criticism to ward the novel is used for further analysis. The data collecting technique is library research. The data analysis uses descriptive technique and content analysis. The outcome of this study is, Danielle Steel in her novel, Fine Things, wants to describe that it is important for someone to take decision based on his own wills. If the person takes wrong decision, it makes her life unpleasant. In her novel Fine Things, Steel's describes the major character as a person who is unable to decide every thing based on his will.